Informal institutions, entrepreneurs’ political participation, and venture internationalization - Li, Dan; Wei, Li-Qun; Cao, Qing; Chen, Deqiu (Journal of International Business Studies, 2022)
Informal institutions such as Guanxi play a critical role in compensating for insufficient formal institutions in emerging markets. Arising from the institutional evolution, Chinese entrepreneurs’ participation in political systems induces the emergence of new types of Guanxi that the entrepreneurs can draw on in internationalizing their new ventures. Drawing from institutional and cognitive decision-making theories, we theorize that the entrepreneurs’ political participation enhances their self-perceived status (willingness) and resource acquisition (ability) in their new ventures’ engagement in high-commitment entry modes. Our analysis of 5,999 Chinese private new ventures offers empirical support for the mediating effects of self-perceived status and resource acquisition on the association between entrepreneurs’ primary and secondary political participation and their ventures’ engagement in high-commitment entry modes. Our research contributes to the international business literature by examining the micromechanism of the interplay between formal and informal institutions and to the international entrepreneurship literature by highlighting the critical role that individual cognition plays in new ventures’ internationalization decision-making.